Assessing levels of mercury in the endangered whooping crane - Smith, Paige E. (My University, 2019)
Whooping cranes (Grus americana) are one of the most charismatic and endangered birds in North America. Currently, there are 594 wild individuals found in four populations, one of which is the eastern migratory population (EMP) that breeds in central Wisconsin. Unfortunately, reproductive success in the EMP has been close to 0%. We hypothesized that mercury, an anthropogenic environmental contaminant, hinders the cranes’ ability to rear offspring to independence. This hypothesis stems from the fact that (1) mercury has been measured in Wisconsin breeding grounds and (2) when methylated, mercury can alter a wide range of behaviors including parental care, foraging, and reproductive success. To test this, we measured total mercury in three whooping crane populations: Aransas- Wood Buffalo (AWBP), the EMP, and captive birds from the International Crane Foundation (ICF). This allowed us to compare birds of known successful reproduction (ICFP), birds of presumed successful reproduction (AWBP), and birds of known low reproduction (EMP). If our hypothesis is true, we predicted that mercury would be higher in the EMP than in the AWB and ICF. Results show elevated levels of mercury in the EMP as compared to the AWBP and ICFP. Our study is novel in that whole blood samples were measured for a baseline in multiple populations of endangered whooping cranes. The results show low levels of mercury in all WHCR populations; however, there is no agreement on what a safe threshold is for humans let alone other mammals or birds. More research is needed to examine the sub lethal effects contaminants such as mercury has on G. americana.
"A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science-Biology."
Keywords: Whooping cranes; Eastern migratory population; Mercury; Wisconsin